Philosophical Essays, Volume 2 : The Philosophical Significance of Language - Soames, Scott (Book collections on Project MUSE., 2009)
The two volumes of Philosophical Essays bring together the most important essays written by one of the world's foremost philosophers of language. Scott Soames has selected thirty-one essays spanning nearly three decades of thinking about linguistic meaning and the philosophical significance of language. A judicious collection of old and new, these volumes include sixteen essays published in the 1980s and 1990s, nine published since 2000, and six new essays. The essays in Volume 1 investigate what linguistic meaning is; how the meaning of a sentence is related to the use we mak.